Values Education as Perceived by Social Studies Teachers in Objective and Practice Dimensions - KATILMIŞ, AHMET (EDAM, 2017)
The purpose of this study was to reveal the objectives of values education in Turkey, values education-related activities performed in schools, and preferred approaches to values education according to the opinions of social studies teachers. This qualitative study used a phenomenological pattern. The participants of the study were selected from social studies teachers working in the province of Istanbul. Because data triangulation was used in the study, separate participants provided qualitative data and quantitative data. The qualitative data were collected using a semi-structured interview form applied to a total of eight participants, 4 female and four male, selected by purposive sampling. Expert opinion was solicited for the development of the semi-structured interview form used in interviews. Quantitative data were collected using a questionnaire, which was found to have a Cronbach's Alpha value of.820, applied to a total of 120 social studies teachers selected via clustering. The data collected using these measurement tools were classified and analyzed, and showed that the participants had ideological approaches and taught values that enabled basic humanitarian values and social structures to be maintained. However, values education activities performed in schools were found to be inadequate, and teachers mostly preferred the infusion approach in values education.
Keywords: Value; Values education; Social studies; Social studies teacher; Primary education; CHARACTER EDUCATION